The Personality Type, Financial Rewards, and Prestige: Factors Influencing Students' Interest in Public Accounting Careers - Lestari, Komang Tri Winda; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p15, 2024)
The increasing number of companies listed on the IDX signifies a growing demand for public accounting services. Despite this, the number of public accountants in Indonesia remains relatively low. This research utilizes the Theory of Planned Behavior and the Big Five Personality Theory to empirically test how personality types, financial rewards, and professional prestige influence students' interest in pursuing a career as public accountants. The study was conducted by the PSSA class of 2020 at Udayana University, using a questionnaire as the research instrument. The sample consisted of 169 respondents, and the data analysis technique employed was Multiple Linear Regression. The findings reveal that personality types, financial rewards, and prestige significantly and positively influence students' interest in a public accounting career. The theoretical implications of this research offer detailed insights into the Theory of Planned Behavior and the Big Five Personality Theory.